The kernel of the m-order trace operator - Roman Tello, Hubert (2021)
In this work, we are interested in prove that the kernel of the trace operator of morder, is the space H0m (Ω) with Ωbounded open well-regular, inspired by the results shown by M. Cavalcanti [14]. Finally, we give some comments.